1993
DOI: 10.1007/bf00000873
|View full text |Cite
|
Sign up to set email alerts
|

The geochemistry of methane in Lake Fryxell, an amictic, permanently ice-covered, antarctic lake

Abstract: Abstract. The abundance and distribution of dissolved CH 4 were determined from [1987][1988][1989][1990] in Lake Fryxell, Antarctica, an amictic, permanently ice-covered lake in which solute movement is controlled by diffusion. CH 4 concentrations were <1 uM in the upper oxic waters, but increased below the oxycline to 936 uM at 18 m. Sediment CH 4 was 1100 #mol (1 sed) -1 in the 0-5 cm zone. Upward flux from the sediment was the source of the CH, NH + , and DOC in the water column; CH 4 was 27% of the DOC + C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
60
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 56 publications
5
60
0
Order By: Relevance
“…Financial support was provided by the National Science Foundation grants DPP 91-18363 and OCE 93-02812. the lakes provide model environments in which to study the biogeochemical cycles of carbon, methane, and sulfur in aquatic systems (Smith et al 1993). However, the physical limnology of the lake, which impinges on the hydrological balances as well as the biogeochemical cycles, is not well understood.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Financial support was provided by the National Science Foundation grants DPP 91-18363 and OCE 93-02812. the lakes provide model environments in which to study the biogeochemical cycles of carbon, methane, and sulfur in aquatic systems (Smith et al 1993). However, the physical limnology of the lake, which impinges on the hydrological balances as well as the biogeochemical cycles, is not well understood.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Such lakes serve as unique model systems for estimating the role of CH 4 in periglacial lacustrine environments during former glacial periods and for evaluating the importance of microbial biogeochemical processes in low-temperature aquatic ecosystems. In contrast with the polar regions of the Northern Hemisphere, there are only a few detailed studies on the occurrence and biogeochemistry of CH 4 in Antarctic lakes and ponds (e.g., Franzmann et al 1991;Smith et al 1993;Galchenko 1994).…”
mentioning
confidence: 99%
“…Such profiles were used by Lawrence and Hendy (1985) to infer a stratified refilling period in the lake's history beginning -1,200 years ago. The water-column temperature increases from 0.4"C at the ice-water interface to 3.4"C between 9 and 10.5 m and then decreases to 2.6"C at the lake bottom (Smith et al 1993;Miller and Aiken 1996). Fluid densities calculated by Aiken et al (1991) show that the water column was density-stable during the summer sampling of 1987.…”
Section: Physical and Limnologic Aspects Of Lakes Hoare And Fryxellmentioning
confidence: 98%
“…Smith et al (1993) reported that fluid electrical conductivity increased with depth and that gradients in salinity remained constant from one season to the next. Solute concentration increased significantly beginning at -6 m and appeared to be diffusionally controlled (Smith et al 1993).…”
Section: Physical and Limnologic Aspects Of Lakes Hoare And Fryxellmentioning
confidence: 99%
See 1 more Smart Citation